2022
DOI: 10.3389/fpsyg.2022.963839
|View full text |Cite
|
Sign up to set email alerts
|

Help-seeking behavior in bereaved university and college students: Associations with grief, mental health distress, and personal growth

Abstract: Many students have experienced the death of a loved one, which increases their risk of grief and mental health problems. Formal and social support can contribute to better coping skills and personal growth in bereaved students. The purpose of this study was to examine the support that students received or wanted to receive and its relation to students’ mental health. We also looked at students’ needs when receiving support and barriers in seeking formal and social support. Participants (N = 666) completed an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…When not included in the proactive follow-up, bereaved friends who still needed help had to seek help on their own initiative. Several studies have shown that bereaved people with strong grief reactions, especially adolescents, may be less likely to seek help on their own (Johnsen & Dyregrov, 2015 ; Tureluren et al, 2022 ), and wish to be offered help (Dyregrov et al, 2015 ; Kaspersen et al, 2022 ; Titlestad et al, 2020 ). Some barriers in regard to seeking help have been suggested to be negative attitudes toward help-seeking, a lack of trust in the healthcare service, feelings of stigmatization, and feeling that people do not believe they are entitled to receive help (Dyregrov et al, 2015 ; Schnyder et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When not included in the proactive follow-up, bereaved friends who still needed help had to seek help on their own initiative. Several studies have shown that bereaved people with strong grief reactions, especially adolescents, may be less likely to seek help on their own (Johnsen & Dyregrov, 2015 ; Tureluren et al, 2022 ), and wish to be offered help (Dyregrov et al, 2015 ; Kaspersen et al, 2022 ; Titlestad et al, 2020 ). Some barriers in regard to seeking help have been suggested to be negative attitudes toward help-seeking, a lack of trust in the healthcare service, feelings of stigmatization, and feeling that people do not believe they are entitled to receive help (Dyregrov et al, 2015 ; Schnyder et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Following sudden and violent deaths, approximately 80–90% of bereaved people report that they do not cope alone, and they especially need help owing to factors such as lack of energy, desperation, and the surreal nature of the experienced situation (Kristensen et al, 2021 ). However, studies indicate that a considerable number of bereaved individuals experiencing prolonged grief or mental health problems do not seek help from help services, or do not prefer professional sources of help (Johnsen & Dyregrov, 2015 ; Reime et al, 2022 ; Tureluren et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, student health services have lower thresholds compared to specialized grief or psychological services. Appropriate training of staff at these health services would be a prerequisite for providing adequate support to the bereaved students [53][54][55].…”
Section: Discussionmentioning
confidence: 99%